"En français, s'il te plaît": the linguistic battlegrounds of Entre les murs. Issue 1 (April 2017) - King, Gemma
Abstract : Representations of language as a tool for exerting social power are steadily increasing in the French cinema of the twenty-first century. In linguistically diverse films like Laurent Cantet's Entre les murs (2008), language is used by institutions to establish hierarchies, and by individuals to undermine them. In such films, both French and other languages can constitute a narrative device in themselves, and a weapon for challenging authority and manipulating others. Such a cinema raises important questions concerning the role of language in today's France. This article examines the ways in which language is harnessed as a tool for both constructing and deconstructing power relationships in the environment of the contemporary French collège in Entre les murs . Within the film's ritualized classroom setting, the bourgeois French teacher and multicultural student cohort use variations of French and other languages, including undervalued slang forms such as verlan and tchatche, to dominate one another and (re) negotiate the social hierarchy. The result is a linguistic battleground, in which the codified power relations of the teacher–student dynamic are undermined. The film thus prompts us to reconsider what it means to "master language" in relation to cinema and the contemporary concept of "Global French."